Glaucoma and Ocular Hypertension in Pseudoexfoliation Syndrome - Khalid I. Talpur, Azfar Ahmed Mirza, Noor Bakht Nizamani, Mariya Nazish Memon, Sajjad Ali Surhio (Pakistan Journal of Ophthalmology, 2021)
Purpose: To assess the frequency of glaucoma and ocular hypertension in pseudoexfoliation syndrome. Material and Methods: This study was conducted in the Department of Ophthalmology, Liaquat University Eye Hospital, Hyderabad, Pakistan from June 2011 to December 2011. Hundred confirmed cases of pseudoexfoliation syndrome (PXS) were included in the study by non-probability convenience sampling. Tonometry, gonioscopy, ophthalmoscopy and visual field analysis were carried out to determine glaucoma. Data was collected by specially designed proforma and analyzed by using Statistical Program for Social Sciences (SPSS, version 16.0 for Windows). The frequencies and percentage were recorded and any association with predisposing factors was statistically analyzed on chi square test. P-value of <0.001 was considered significant with a confidence interval (CI) of 95%. Results: Out of the 100 PXS patients, 16% patients were diagnosed with pseudoexfoliation glaucoma (PXG) (CI 95%): 12% with open angle glaucoma and 4% narrow angle glaucoma. Ocular hypertension without glaucomatous changes was detected in 9% (CI 95%) of the patients (P <0.001). PXG was more common after 50 years of age while ocular hypertension occurred earlier i.e. 40 years. Gender (P=0.45), locality (P=0.725) and family history of glaucoma (P=0.95) were statistically insignificant risk factors for development of glaucoma in PXS patients. Increased age, intraocular pressure and cup-disc ratio (16%) were significant risk factors for development of PXG (P <0.001 CI 95%). Conclusion: Increasing age, intraocular pressure and cup disc ratio are significant risk factors for development of glaucoma in PXS. It is recommended that patients over 50 years should be actively examined for glaucoma particularly those with PXS. Keywords: Pseudoexfoliation syndrome, Glaucoma, Ocular Hypertension.